Diet or additional supplement to increase potassium intake: protocol for an adaptive clinical trial - Hiremath, Swapnil; Fergusson, Dean; Knoll, Greg; Ramsay, Tim; Kong, Jennifer; Ruzicka, Marcel (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background High blood pressure is the leading cause of cardiovascular disease worldwide. The prevalence of high blood pressure is steadily rising as the population grows amongst older adults with the ageing population. Therapeutical treatments are widely available to decrease blood pressures, in addition to many lifestyle options, such as dietary changes and exercise. There is a marked preference amongst patients, as reiterated by Hypertension Canada, for more research into non-therapeutic methods for controlling blood pressure or to reduce the burden of taking many pills to control high blood pressure. Indeed, effective options do exist, especially with diet, specifically decreasing sodium and increasing potassium intake. Current public health outreach primarily focusses on sodium intake, even though potassium intake remains low in the Western world. Excellent data exist in published research that increasing potassium intake, either via dietary modification or supplements, reduces blood pressure and reduces risk of cardiovascular outcomes such as stroke. However, the advice most often provided by medical professionals is to ‘eat more fruits and vegetables’ which has little impact on patient outcomes. Methods We propose to do a clinical trial in two stages with an adaptive trial design. In the first stage, participants with high blood pressure and proven low potassium intake (measured on the basis of a 24-h urine collection) will get individually tailored dietary advice, reinforced by weekly supportive phone/email support. At 4 weeks, if there has not been a measured increase in potassium intake, participants will be prescribed an additional potassium supplement. Testing will be conducted again at 8 weeks, to confirm the efficacy of the potassium supplement. Final measurements will be planned at 52 weeks to observe and measure the persistence of the effect of diet or additional supplement. Concurrent measurements of sodium intake, blood pressure, participant satisfaction, and safety measures will also be done. Discussion The results of the study will help determine the most effective method of increasing potassium intake, thus reducing blood pressure and need for blood pressure-lowering medicines, and at the same time potentially increasing participant satisfaction. The current guidelines recommend changes in diet, not a potassium supplement, to increase potassium intake; hence, the two-stage design will only add supplements if the most rigorous dietary advice does not work. Trial registration This study has been registered on ClinicalTrials.gov NCT03809884 . Registered on January 18, 2019